Pengaruh Kombinasi Takaran Urea dan Asam Humat Terhadap Pertumbuhan dan Hasil Pakcoy (Brassica rapa L.) - Irpan Nudin; Desi Rahmawati; Dede Mulyati; Yuli Ratna Nawangsari (Agrisintech (Journal of Agribusiness and Agrotechnology), 2026)
ABSTRACT In efforts to increase crop production, it is currently hampered by various obstacles, including low levels of soil organic matter and inefficiency in the use of inorganic fertilizers such as nitrogen fertilizers. Humic acid can be an alternative to these problems because humic acid has a very high CEC (more than 200 meq/100 g) so that it can be used to slow down the release of nitrogen. Thus, humic acid can increase the efficiency of nitrogen fertilizers and at the same time increase the levels of soil organic matter. The purpose of this study was to determine the effect of a combination of urea and humic acid fertilizer doses on the growth and yield of pak choi plants. This experiment was carried out from February to March 2025. The experiment was carried out using a Simple Randomized Block Design consisting of twelve treatment combinations and three replications. Observation data were analyzed using the F Test and if there was a difference between the treatments, it was continued with the Duncan Multiple Range Test with a 95% confidence level. Observation data were analyzed using the F Test and if there was a difference between treatments, it was continued with Duncan's Multiple Range Test with a 95% confidence level. The results of the study showed that the combination treatment of urea and humic acid fertilizer doses had no effect on the growth and yield of pak choy plants. Keywords: humic acid, pak choi, urea